From War to the Rule of Law Peace Building after Violent Conflicts - Raad voor het Regeringsbeleid, Wetenschappelijke (WRR Rapporten, 2007)
As recent events in Iraq demonstrate, countries that have suffered civil war or rule by military regime can face a long, difficult transition to peaceful democracy. Drawing on the experiences of Bosnia, Haiti, Rwanda and Afghanistan, this outstanding volume demonstrates that newly emerging democracies need more than emergency economic support: restoring the rule of law can involve the training of a new police force, for example, or the creation of an international war crimes tribunal. Concluding with specific recommendations for the UN and EU members,Voorhoeve reminds us that disregard for human rights or delay in civilian reconciliation can lead to resurgences of violence. This title is available in the OAPEN Library - http://www.oapen.org.